Penyuluhan Fisioterapi Terkait Manfaat Exercise untuk Meningkatkan Keseimbangan dan Fleksibilitas pada Lansia di Desa Celep - Mida Wati; Rinna Ainul Maghfiroh; Sartini Sartini (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
The decline in balance and flexibility is a common issue among the elderly, increasing the risk of falls and injuries. This community service activity aimed to raise awareness and knowledge among the elderly in Celep Village about the importance of balance and flexibility exercises through physiotherapy education. The methods used included the delivery of educational materials, distribution of leaflets, exercise demonstrations, and pre- and post-tests to measure knowledge improvement. The results showed a significant increase in participants’ understanding across all indicators, with post-test scores exceeding 96%. This activity demonstrates that simple, self-administered education and exercises are effective in improving elderly awareness of the importance of maintaining body balance and flexibility. This intervention is expected to be implemented sustainably to support the quality of life in the elderly.